Analisis Tingkat Pelayanan IT Service Management Pada Penerapan Ujian Satuan Pendidikan Menggunakan Kerangka Framework ITIL V3 di SMK Negeri 8 Palembang - Yunita Permata Sari; Tata Sutabri (Institute of Advanced Knowledge and Science, 2023)
Education Unit Examination is a test or evaluation conducted within an education unit, such as a school or other educational institution. The information technology service used by SMK Negeri 8 for the education unit exam is the CBT BeeSmart application. However, the CBT BeeSmart application at SMK Negeri 8 Palembang is not optimally used. Therefore, it is necessary to analyze information technology-based CBT BeeSmart service management to determine the performance or quality of CBT BeeSmart information technology services. This research uses the ITIL V3 framework in the application of the education unit exam at SMK Negeri 8 Palembang. The domain in the ITIL V3 framework used in this research is the service operation domain. The method used is descriptive qualitative with data collection techniques, through interviews and observations. Based on the results of 3 research processes, namely Event Management, Request Fulfilment and Problem Management, it is necessary to increase the need for hardware, software, infrastructure and increase the competence of Human Resources.